Protective role of remogliflozin against experimental liver fibrosis by activating AMPK/SIRT1/Nrf2 and suppressing NF-κB pathways - ALSuhaymi, Naif; Alsugoor, Mahdi H.; Shokry, Aya A.; Fayed, Hany M.; Mohamed, Bassim M. S. A.; Afifi, Sherif M.; Esatbeyoglu, Tuba; Korany, Reda M. S.; Elbaset, Marawan A. (Frontiers in Pharmacology, 2025)
Liver fibrosis is considered an epidemic health problem since it can lead to several insults that can be fatal. Remogliflozin (Remo), an inhibitor of the sodium–glucose cotransporter 2 (SGLT2) protein, is one of the most recently developed antidiabetic drugs for treating type 2 diabetes mellitus (T2DM). The antidiabetic and antioxidant impacts of Remo have been demonstrated in numerous animal models; however, its antifibrotic activity remains unclear. Therefore, we planned this study to clarify the preventive activity of Remo against thioacetamide (TAA)-induced liver fibrosis in male rats, along with its anticipated pathways. Four groups of rats (n = 6) were used in our investigation: the control group; the TAA group, which received 100 mg/kg b.wt IP twice a week for 6 weeks; and the TAA + Remo groups, which were given two doses of Remo at 25 and 50 mg/kg b.wt orally, respectively, for 4 weeks in addition to TAA injections. The TAA group showed a marked increase in liver enzymes, lipid peroxidation, and proinflammatory cytokines, along with a marked decrease in albumin and cellular antioxidant status. Additionally, the TAA group showed a marked increase in nuclear factor-κB (NF-κB) and a marked decrease in AMP-activated protein kinase (AMPK), sirtuin 1 (SIRT1), and nuclear factor erythroid 2–related factor 2 (Nrf2) levels and expressions. The harmful effects of TAA were significantly mitigated by Remo therapy, which improved the aforementioned parameters. Histopathological findings corroborated the biochemical results. The results of our study suggest that Remo has anti-inflammatory and antioxidant properties that protect against TAA-induced liver fibrosis by inhibiting the NF-κB pathway and activating the AMPK/SIRT1/Nrf2 pathway.